Expression of CCR6 in esophageal squamous cell carcinoma and its effects on epithelial-to-mesenchymal transition - Liu, Jian (Oncotarget, 2017)
Esophageal squamous cell carcinoma (ESCC) is the most common esophageal cancer associated with poor prognosis. We detected the expression of C-C motif chemokine receptor 6 (CCR6) and epithelial-to-mesenchymal transition (EMT) markers in esophageal tissues/cells, and evaluated the effects of CCR6 on ESCC cells proliferation, migration and invasion in response to C-C motif chemokine ligand 20 (CCL20) treatment. Our data showed CCR6 was highly expressed in ESCC cell lines (ECA-109 and TE-1), whereas kept in a low expression in normal cell lines HEEC (P < 0.001). CCL20 stimulus induced a significant decrease in the proliferation ability of ESCC (P < 0.05). The healing speed of CCL20 group was significantly higher than control in ECA-109 (P < 0.01), whereas significantly lower in αCCR6+CCL20 group than CCL20 group (P < 0.05).The number of cells permeabling through the polycarbonate membrane in CCL20 group was higher than control (P < 0.01). The cell number in αCCR6+CCL20 group was significantly reduced compared to CCL20 group in ECA-109 (P < 0.05). Moreover, after CCL20 stimulated in ECA-109, both mRNA and protein level of E-cadherin significantly decreased compared to control, while Vimentin was significantly higher. In αCCR6+CCL20 group, mRNA and protein level of E-cadherin significantly increased compared to CCL20 group, while Vimentin was much lower than CCL20 group. There was no significant difference in TE-1. In summary, high expression of CCR6 existed in the lymph node metastasis and TNM stage of ESCC. CCR6 play an important role in the regulation of tumor cell proliferation, invasion and migration. CCR6 may participate in regulating the occurrence of EMT in ESCC.